To aid, insure, transfer, or control : what drives the welfare state? - Edward Castronova (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
The paper uses panel data on OECD countries to assess four theories about the forces that generate social spending. The four theories are: Aid: the Welfare State is about helping the poor. Insure: the Welfare State insures the consumption of middle-class voters. Transfer: the Welfare State transfers money to politically-powerful entitled groups. Control: the Welfare State is about controlling the behavior of the underclass. The data give the following grades: Aid D-, Insure C+, Transfer A-, Control D. This assessment is made by regressing the share of social spending in GDP on a vector of country characteristics. The methods involve simultaneous equation fixed-effects models, and they take advantage of some recent innovations in the growth literature involving the treatment of country-level panel data
Keywords: H5; I3; 330; Sozialstaat; Öffentliche Sozialausgaben; Public Choice; Schätzung; Industriestaaten